Presentation and Outcomes of Elderly Patients Undergoing Head and Neck Surgeries: A National Perspective. (August 2020) - Al-Qurayshi, Zaid; Sullivan, Christopher Blake; Schwalje, Adam; Walsh, Jarrett; Bayon, Rodrigo; Tufano, Ralph; Kandil, Emad
Objectives: To examine clinical profile and outcomes of elderly patients (65-90 years) undergoing head and neck surgeries in the United States. Study Design: A retrospective cross-sectional analysis. Setting: The Nationwide Readmissions Database, 2010 to 2015. Subjects and Methods: Adult (≥18 years) patients who underwent head and neck surgeries. Analysis included χ 2 test and logistic analysis. Results: A total of 113, 602 and 32, 580 patients <65 and ≥65 years old, respectively, were included. Patients ≥65 years old were more likely to have multiple comorbidities (62.8% vs 32.6%, P < .001) and to present with head and neck cancer (19.8% vs 11.4%, P < .001). The most common comorbidity was diabetes (21.0%). The most common cancer types by site were mouth (29.12%), thyroid (28.08%), and nonmelanoma skin cancer (13.22%). The percentage of geriatric patients who underwent head and neck surgeries increased from 21.8% in 2010 to 25.0% in 2015 ( P < .001). A total of 5450 (16.85%) patients developed postoperative complications, and the most common complications were pulmonary related (10.55%), bleeding (6.96%), acute renal failure (6.01%), and infection (3.97%). Blood transfusion was required in 3.53% of the patients. Readmission prevalence was 0.32%, and mortality risk was twice as likely (odds ratio, 2.05; 95% confidence interval, 1.77-2.38; P < .001). Independent risk factors of mortality were older age, multiple comorbidities, type of surgery, blood transfusion, and tracheostomy ( P < .05, each). Conclusion: Elderly patients currently represent 25% of patients admitted for head and neck surgery. This population should be provided with a different level of care due to a higher risk of complications and mortality.